Implementation of Citizenship Education Learning to Improve Cognitive Abilities and Social Concern in Children - Harahap, Hasniah Khairani (International Journal of Students Education, 2024)
This study aims to analyze the application of citizenship education in improving children's cognitive abilities and social awareness. Civic education is an important aspect in character building and social awareness in children. In this study, the literature review approach method was used because this study aims to analyze the role of citizenship education in improving children's cognitive abilities and social awareness. Civic education has an important role in shaping the attitudes, knowledge, and social skills that children need to actively participate. In this study, several studies were conducted that focused on citizenship learning, its influence on cognitive development, and its impact on children's level of social awareness. This study shows that citizenship education makes a positive contribution to critical thinking skills and the development of empathy in children. Through appropriate methods, such as discussions and case studies, children can better understand the concept of citizenship, thereby increasing social awareness and the ability to interact with the surrounding environment. This research is expected to be a reference in developing more effective learning methods in citizenship education, so as to optimally support children's cognitive development and social awareness and be able to improve children's cognitive understanding of basic citizenship concepts, such as the rights and responsibilities of a student.